Karakteristik Anak Bungsu - Nilma Zola; Asmidir Ilyas; Yusri Yusri (Jurnal Konseling dan Pendidikan, 2017)
Each child in the birth order has advantages and disadvantages, but the most often attracts attention in the family is the youngest child. The phenomenon found in the presence of younger children who lack the motivation of achievement, less independent, likes to seek the attention of others, and difficult to adapt in new environment and lack of willingness in taking responsibility. The type of this research is descriptive quantitative. Research subjects of all youngest children at Junior High School totaling 107 people. The results reveal that, (1) independence is generally in the category of less good; (2) adaptation in school is generally in very good category; (3) achievement motivation is generally in the less good category; and (4) responsibility in learning is generally in the good category.